CAROL RAMA: BETWEEN SEXUALITY, MADNESS AND PAIN - Rago, Margareth (História: Questões e Debates, 2018)
Long ignored by the critics of art, the artistic production of Carol Rama (1918-2015) gains prominence in exhibitions and in feminist interpretations. It is highlighted, in her work, issues related to sexuality, erotic fantasy, lust in the relationship between genders, male masturbation and sensualized exhibition of naked bodies, associated with madness and sexual perversion. Foucault’s reflections and conceptual operators allow us to launch a more in-depth look at this transgressive artistic production and show the striking criticism that the Italian artist launches to the dispositif of sexuality, the biopower and eugenicist science. As shown by the philosopher, in his critical reading of both medical science and Christianity, since the 19th century, the normalizing processes were leaned on medical-psychiatric notions, such as psychopatia sexualis, updating misogynist narratives about original sin and the figure of Eve, almost always accompanied by the serpent. I explore these themes regarding the pictorial art of Carol Rama, seen as a practice of female freedom.